IMPLIKASI KEDUDUKAN GUBERNUR DAERAH ISTIMEWA YOGYAKARTA TERHADAP DEMOKRATISASI DAN EFEKTIVITAS PEMERINTAHAN DAERAH ISTIMEWA YOGYAKARTA - Sofie Dwi Rifayani; Priyatno Harsasto; Rina Martini (Journal of Politic and Government Studies, 2013)
Governor multiple appointments by Sri Sultan Hamengku as King of Kasultanan is one ofDaerah Istimewa Yogyakarta’s privileges. In one side, Daerah Istimewa Yogyakarta is able toimplement the democracy in daily lives. But in other side, the absences of elections as oneelement of the democracy, bring out the questions about governmental process which isdemocratic and effective in Daerah Istimewa Yogyakarta. Courteous attitude owned by thepeople and legislative institution causing minimum control system for executive institution. Atthe end, we need to find formula of the implication dualism Governor positions by King ofKasultanan towards democratic and government effectiveness in Daerah Istimewa Yogyakarta.Keywords: Daerah Istimewa Yogyakarta, democratic, government effectiveness